Differences in play can illuminate differences in affiliation: A comparative study on chimpanzees and gorillas - Cordoni, Giada (PLoS One, 2018)
Play behaviour reinforces social affiliation in several primate species, including humans. Via a comparative approach, we tested the hypothesis that play dynamics in a group of lowland gorillas (Gorilla gorilla gorilla) are different from those in a group of chimpanzees (Pan troglodytes) as a reflection of their difference in social affiliation and agonistic support. We selected one group of lowland gorillas and one of chimpanzees, hosted at the ZooParc de Beauval (France), managed in a similar way and living in similar enclosures. The same observers video-collected and analysed data on play behaviour in both groups, by applying identical methodological procedures. Data showed that adult play was less frequent in the group of gorillas compare to chimpanzees. Polyadic play, which involves more than two players and is characterised by the most uncertain outcome, was also less frequent in gorillas than chimpanzees. Play sessions were more unbalanced (more unidirectional patterns by one of the player towards the other) in chimpanzees than in gorillas but in the latter play escalated more frequently into serious aggression. Play asymmetry in the gorilla group increased as the number of players increased, which explains why gorillas limited their polyadic playful interactions. In conclusion, our findings on the study groups of apes can be a valuable starting point to expand the study of social play in the great apes to evaluate if inter-individual affiliative relationships really account for the differences in play distribution and dynamics.